Parametric Analysis on Hydrogen Production using Mixtures of Pure Cellulosic and Calcium Oxide - Rashidi, Nor Adilla (2012)
As the fossil fuels kept on depleting, intense research in developing hydrogen (H2) as the alternative fuel has been done to cater our tremendous demand for fuel. The potential of H2 as the ultimate clean fuel differs with the fossil fuel that releases significant amounts of carbon dioxide (CO2) into the surrounding and leads to the global warming. The experimental work was carried out to study the production of H2 from palm kernel shell steam gasification at different variables such as heating rate, steam to biomass ratio and adsorbent to biomass ratio. Maximum H2 composition which is 61% (volume basis) was obtained at heating rate of 100oCmin-1, steam/biomass of 2:1 ratio, and adsorbent/biomass of 1:1 ratio. The commercial adsorbent had been modified by utilizing the alcohol-water mixture. Characteristics of both adsorbents were investigated and it is concluded that flowability and floodability of modified CaO is significantly improved.